Robust standing control with posture optimization. (24th January 2017) - Kavafoglu, Zumra; Kavafoglu, Ersan; Egges, Arjan
Abstract: Humans need to shift their center of mass during standing for several purposes such as preparing for the upcoming motion or increasing their stability. In this paper, we present a control strategy for robust center of mass shifting motions during standing. In our strategy, the desired posture can be defined with only a few high level features, such as the desired character center of mass position and the foot configurations. An online optimization process is designed for generating a kinematic lower body and pelvis posture that satisfies these high level features together with some criteria that guide a natural standing pose. Natural knee bending behaviours automatically arise as a result of this optimization process. Internal joint torques for tracking this optimized posture together with the given desired upper body pose are calculated by the physics‐based control framework. Moreover, a physics‐based arm control strategy that regulates the angular momentum of the character is devised in order to increase the robustness of the character under external disturbances. Several experiments are conducted to demonstrate the effectiveness of the proposed strategy. Because the strategy does not include any off‐line parameter optimization, equations of motion, or inverse dynamics, it is highly suitable for online applications. Abstract : We present a physics‐based approach for robust center of mass shifting during standing. Desired standing posture is defined by a number of high‐level features and an online optimization process calculates the kinematic postures for the lower body and the pelvis. A physics‐based arm control strategy is devised for increasing the robustness of the character. The proposed approach results in robust standing motions with automatic knee‐bending behavior as the character shifts its center of mass in all dimensions.